MANAGING WASTE WITH THE CONCEPT OF REDUCE, REUSE, RECYCLE (3R) AS AN EFFORT TO CREATE A CLEAN ENVIRONMENT - Gonibala, Windarsi; Igirisa, Irawaty; Isa, Rusli (Public Policy Journal, 2024)
This study aims to find out and analyze the effectiveness of waste management with the concept of Reduse, Reuse, Recycle (3R) in Gorontalo City. This study uses a qualitative method whose data is sourced from primary data and secondary data derived from field findings. The results of the research found that the effectiveness of waste management with 3R has not been effective because it has not made significant progress. Public understanding of waste management programs with the concept of Reduce, Reuse, and Recycle in Gorontalo City is still minimal, including urban and rural communities, as well as certain sectors that produce large volumes of waste (e.g. markets, restaurants, schools). Waste management with the 3R concept is still not fully said to be effective because of several things, such as budgeting, public awareness, and the government's seriousness to create a healthy Gorontalo City, so it is necessary to have the role of all levels of society to pay more attention to the waste problem in the city of Gorontalo. So that Gorontalo City in the future becomes a clean city that is free of waste.